2021
DOI: 10.1186/s12905-021-01492-1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of changing pregnancy intentions among women living with HIV in Canada

Abstract: Background Women with an undetectable viral load can become pregnant and have children with no risk of HIV transmission to their sexual partners and low risk of transmission to their infants. Contemporary pregnancy intentions of women living with HIV in Canada are poorly understood, evidenced by high rates of unintended pregnancy and low uptake of contraceptives. Methods We used longitudinal survey data from the Canadian HIV Women’s Sexual and Repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
(66 reference statements)
0
6
0
1
Order By: Relevance
“… 52 Such intentions are highly dynamic with two-fifths of women changing their pregnancy intentions within 3 years of follow-up. 53 Despite these varying reproductive intentions, nearly half of women living with HIV had never discussed their reproductive goals with a healthcare provider since being diagnosed with HIV. 52 Also, 42% reported they did not currently have a healthcare provider they felt comfortable speaking to about reproductive goals.…”
Section: Methodsmentioning
confidence: 99%
“… 52 Such intentions are highly dynamic with two-fifths of women changing their pregnancy intentions within 3 years of follow-up. 53 Despite these varying reproductive intentions, nearly half of women living with HIV had never discussed their reproductive goals with a healthcare provider since being diagnosed with HIV. 52 Also, 42% reported they did not currently have a healthcare provider they felt comfortable speaking to about reproductive goals.…”
Section: Methodsmentioning
confidence: 99%
“…We believe that discussions about pregnancy should not need to wait until a woman asks her physician or nurse, but should be proactively started by healthcare providers. Previous research has found that reproductive discussions are not routine and account for the largest measured gap in comprehensive healthcare for WLWH [35].…”
Section: Discussionmentioning
confidence: 99%
“…No significant association was observed between demographic-socio-economic characteristics and fertility intention. Previous studies, on the other hand, showed a close link between gender and perceived stigma from healthcare providers [ 8 , 23 , 24 ]. These disparities by gender also could have accounted for the stronger association among the husbands compared to the wives.…”
Section: Discussionmentioning
confidence: 99%
“…In Chinese society and culture, wives are primarily reliant on their husbands for fertility [25][26][27]. Furthermore, it seems that the wives' fertility intention was more influenced by the efforts of their husbands to address stigma, fertility desire, and fertility intention [24,28] than from other factors. Only minor differences were found in fertility intention between HIV-positive versus HIVnegative husbands.…”
Section: Plos Onementioning
confidence: 99%